The The Rise of E-Commerce in Bangladesh and Its Expansion - Rahman, Mahmudur (Journal of Management and Administration Provision, 2023)
This article delves into the multifaceted realm of E-commerce in Bangladesh, tracing its evolution from conceptualization to present expansion. Employing a comprehensive methodology, the study relies exclusively on secondary data, drawing insights from a diverse array of national and international sources such as research publications, censuses, websites, blogs, journals, and newspapers. Leveraging the power of the internet as an additional source, our exploration encapsulates the conceptualization and historical narrative of E-commerce in the country. As we navigate the growth and current scenario of E-commerce in Bangladesh, a spotlight is cast on the vibrant activities shaping the digital landscape. The article further unveils the contemporary status of Bangladesh's top E-commerce platforms, providing a snapshot of their current operations and influence. However, woven into the narrative are the challenges faced by the burgeoning E-commerce sector. The discussion delves into the logistical intricacies, regulatory challenges, and cybersecurity concerns that demand attention for sustainable growth. In this context, the article emphasizes the need for a robust policy framework to navigate the evolving dynamics of E-commerce in Bangladesh. In essence, this article offers a nuanced exploration of the rise and expansion of E-commerce in Bangladesh, offering valuable insights into its past, present, and the imperative considerations for its future trajectory.